Cervical Lymphadenopathy-A Clue to Systemic Diseases: A Recent Update - Shazina Saeed1 , Shamimul Hasan2 , Rajat Panigrahi3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Lymph nodes are distributed along with the lymphatic system all over the body. Enlargement of lymphnodes (lymphadenopathy) may result from an infection, hyperplasia during the immunologic response, andsometimes also by infiltration by cancer cells or lipid cells. Lymphadenopathy may be regional or generalizedand or caused by local or systemic factors. Therefore, the differential diagnosis of lymphadenopathy iscritical. Oral physician during routine physical examination also includes the examination of any enlargedlymph node in the head and neck region. Lymphadenopathy may be the only clinical presentation or oneof the few findings, and enlarged lymph nodes may often raise the suspicion of an underlying pathologylike lymphoma, leukemia, and Acquired Immunodeficiency Syndrome (AIDS). This review focuses on thevarious causes of cervical lymphadenopathy, and the systemic approach to the differential diagnosis and themanagement along with the health care team.